Extraordinary majoid crabs: the genus Esopus A. Milne-Edwards, 1875 in the new subfamily Esopinae subfam. nov., and erection of Paulitinae subfam. nov. (Crustacea, Decapoda, Brachyura, Majoidea, Inachoididae Dana, 1851) - Guinot, Danièle; van Bakel, Barry (Zootaxa, 2020)
A rare small species, Esopus crassus A. Milne-Edwards, 1875, recently collected by KARUBENTHOS Expedition 2015 in Guadeloupe, is re-examined. The genus Esopus A. Milne-Edwards, 1875, currently included in the Epialtidae MacLeay, 1838, must be assigned to the Inachoididae Dana, 1851, a rather basal family within the Majoidea Samouelle, 1819, but deviates from the morphotype that is being traditionally associated to this group. It deserves its own subfamily, Esopinae subfam. nov., besides other inachoidid subfamilies, for which a description is here provided (Collodinae Stimpson, 1871; Dasygyiinae Holmes, 1900; Inachoidinae Dana, 1851; Salaciinae Dana, 1851; Stenorhynchinae Dana, 1851). Another inachoidid subfamily is erected here, Paulitinae subfam. nov., for the genus Paulita Guinot, 2012, monotypic with P. tuberculata (Lemos de Castro, 1949, as Dasygyius tuberculatus). A reliable fossil member is recorded from the lower Miocene onwards.